E-commerce and its role during the COVID-19 pandemic in Indonesia - Yasuyuki Sawada; Yesim Elhan-Kayalar; Matthew Shum; Daniel Yi Xu (Asian Development Bank (ADB), 2023)
Micro, small, and medium-sized enterprises (MSMEs) are recognized as crucial drivers of economic development, particularly in low- and middle-income countries. The advent of digital platforms, characterized by economies of scale and significant cross-network externalities in two-sided markets, has brought about unprecedented changes to people's daily lives, employment, businesses, and markets. These transformations have unlocked opportunities for MSMEs. In this paper, we analyze the dynamics of e-commerce and how they unfolded during the coronavirus disease (COVID-19) pandemic, using a unique, composite dataset focusing on GoFood merchants in Indonesia. This paper makes a notable contribution by expanding the analysis of the platform efficiency contributions into static efficiency and dynamic efficiency perspectives. Our analysis reveals three key findings. First, online platforms like Gojek offered a novel form of social safety nets for MSMEs. Second, as the COVID-19 pandemic intensified, we observed market congestion externalities and cannibalization tendencies. Third, women- and men-owned businesses opted for different crisis-mitigation and coping strategies. Vulnerable microenterprises, often owned by women merchants with limited support networks and business assets, were disproportionately affected by the pandemic. Overall, our study demonstrates that the rapid acceleration of digital transformation during the COVID-19 pandemic presents unique research opportunities on distributive justice, external effects, and scale economies, as well as related competition policies.
Keywords: D22; D63; L26; L25; 330; digital platform; distributive justice; e-commerce; platform economies; MSMEs; scale economies; two-sided network externalities; competition policy; COVID-19 pandemic